The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31224/osf.io/x69nu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rationally designed ultra-short pulsed laser patterning of zirconia-based ceramics tailored for the bone-implant interface

Abstract: Ceramic composite materials are increasingly used in dental restoration procedures, but current ceramic surface designs do not yet achieve the osseointegration potential of state-of-the-art titanium implants. Rapid bone tissue integration of an implant is greatly dependent on its surface characteristics, but the material properties of ceramic composite materials interfere with classical surface modification techniques. Here, ultra-short pulsed laser machining, which offers a defined energy input mitigating a h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…[ 28 ] Similar behavior has previously been observed when laser‐texturing the surfaces of zirconia. [ 29 ] Other studies have shown that hydrophilic surfaces can be obtained using laser‐texturing by generating smoother surface features, with roughness values < 0.5 µm. [ 10 ] The modified WCA was expected to influence biological interactions with the surface, in particular the interaction with blood, which was previously shown to be enhanced on hydrophilic surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] Similar behavior has previously been observed when laser‐texturing the surfaces of zirconia. [ 29 ] Other studies have shown that hydrophilic surfaces can be obtained using laser‐texturing by generating smoother surface features, with roughness values < 0.5 µm. [ 10 ] The modified WCA was expected to influence biological interactions with the surface, in particular the interaction with blood, which was previously shown to be enhanced on hydrophilic surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…But the ceramic implants failed to perform clinically due to difficulty in threading, limited osseointegration, greater elastic modulus compared to titanium, and associated stress shielding. Although bioactivity and bone‐bonding efficacy of zirconia could be improved with various surface modifications, 5–8 modulus could not be altered as it is an inherent material property of metal oxides and requires innovations in structural and designing aspects for its modulation.…”
Section: Introductionmentioning
confidence: 99%